(untitled) (Journal of Engineering, 2006)
Aluminum-magnesium alloy has been anodized using chromic acid as an electrolyte. The effect of voltage in the range of 15-60V, electrolyte concentration in the range of 20-110 g/l, electrolyte temperature in the range of 30-60 °C and time of exposure in the range 25-85 minutes on the coating weight of the anodic film are studied. The experimental data was fitted in terms of the coating weight and the coefficients of third order polynomial are estimated. Optimum conditions of the studied variables are predicted and found equal to 32V, 85 g/1, 50 °C and 70 minutes.